Introduction to Cryptography: Principles and Applications - Delfs, Hans; Knebl, Helmut (Information Security and Cryptography, 2007)
Modern cryptography provides essential techniques for securing information and protecting data. This book provides an introduction to the key concepts of cryptography, from encryption and digital signatures to cryptographic protocols, such as electronic elections and digital cash. It applies probability theory to make basic notions precise, such as the security of cryptographic schemes. More advanced topics are also addressed, such as the bit security of one-way functions and computationally perfect pseudo-random generators. No special background in mathematics is needed to understand the material; an explanation of the necessary mathematics is given in two appendices. In addition, to make the material readily accessible, the authors use the same examples throughout the book and provide complete proofs.It will be an ideal textbook for an undergraduate course in cryptography as well as a guide to those wanting an introduction to the subject.